2000
DOI: 10.1289/ehp.00108s2161
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene and cancer: epidemiologic evidence.

Abstract: Trichloroethylene is an organic chemical that has been used in dry cleaning, for metal degreasing, and as a solvent for oils and resins. It has been shown to cause liver and kidney cancer in experimental animals. This article reviews over 80 published papers and letters on the cancer epidemiology of people exposed to trichloroethylene. Evidence of excess cancer incidence among occupational cohorts with the most rigorous exposure assessment is found for kidney cancer (relative risk lRR] = 1.7, 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 93 publications
10
157
2
2
Order By: Relevance
“…Past case-control and cohort studies have suggested an association with exposure to solvents and paints (5,(41)(42)(43). A recent study in the Netherlands found a nonsignificant excess for those exposed to paint components (33).…”
Section: Cases (N)mentioning
confidence: 99%
“…Past case-control and cohort studies have suggested an association with exposure to solvents and paints (5,(41)(42)(43). A recent study in the Netherlands found a nonsignificant excess for those exposed to paint components (33).…”
Section: Cases (N)mentioning
confidence: 99%
“…For example, liver and lungs are primary target organs in male mice whereas kidneys are primary target organs in male rats. Potential target organs in humans include kidneys, liver, cervix, and hematopoietic cells (i.e., non-Hodgkin's lymphoma) (Wartenberg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A moderately increased risk has been observed in several mortality and incidence studies among workers exposed to trichloroethylene, but inconsistencies in findings across the study populations and some methodological limitations complicate the interpretation of the findings. [2][3][4][5][6] Excesses of liver cancer have also been reported among workers potentially exposed to tetrachloroethylene, [7][8][9] but in general, the epidemiologic literature on this association is not consistent. [10][11][12][13][14] Carbon tetrachloride, chloroform and 1,2-dichloroethane have been classified as possibly carcinogenic to humans by the International Agency for Research on Cancer (IARC), and liver tumors have been detected in some animal experiments.…”
mentioning
confidence: 99%